Ti3C2Tx with a hydroxyl-rich surface for metal sulfides as high performance electrode materials for sodium/lithium storage. Issue 24 (10th June 2021) - Han, Qi; Zhou, Yanli; Du, Rong; Xiao, Bo; Cheng, Jianbo; Zhang, Ming; Dong, Caifu; Sun, Xueqin; Jiang, Fuyi; Yang, Jian
Abstract : Three kinds of Ti3 C2 T x modified metal sulfide composites have been prepared via a universal one-step strategy. Abstract : Three kinds of Ti3 C2 T x modified metal sulfide composites have been prepared via a universal one-step strategy. First, three Ti3 C2 T x MXene supported MoS3 composites with different surface F/O ratios and layer distances are synthesized. The abundant –OH groups on the surface of LiOH-treated Ti3 C2 T x facilitate the effective bonding with MoS3, forming a robust sandwich-like structure (LF/O-Ti3 C2 T x /MoS3 ). As anode material for sodium-ion batteries (SIBs), it shows outstanding long-term cycling performance in comparison with the other two Ti3 C2 T x supported MoS3 composites. Its reversible capacity can be maintained at 611 mA h g −1 after 1000 long cycles at 2 A g −1, obviously superior to those of single LF/O-Ti3 C2 T x and MoS3 . Besides SIBs, LF/O-Ti3 C2 T x /MoS3 also exhibits satisfying lithium storage performance. Kinetics analysis and theoretical calculation further explain the outstanding performance of LF/O-Ti3 C2 T x /MoS3 . Moreover, LF/O-Ti3 C2 T x modified CuS/SnS2 composites also show similar and excellent electrochemical results for SIBs and LIBs. This facile synthesis strategy opens a door to prepare high-performance Ti3 C2 T x supported conversion-type anode materials for large-scale energy storage.